Evaluating the Impact of a Country’s Scientific Activity on the Provision of Its Economic Security - Victoria KHAUSTOVA; Olena RESHETNYAK; Roman LOBODIN (Communications of International Proceedings, 2020)
The purpose of the article is to assess the impact of individual countries’ scientific activity on their economic security. Research methods are as following: index method, ranking, cluster analysis and regression models development. The research of the dependence of a country’s economic security on the science development level includes the following stages: calculating the science development index; determining groups of countries depending on the science development level; modeling economic security depending on the level of a country’s science development. In the work based on the development of regression models the hypothesis about the influence of scientific developments on the economic security indices is confirmed. The calculation of the world countries’ scientific development index was carried out which is a complex index and includes scientific potential evaluation, scientific activity results and evaluation of scientific activity and potential growth rates for 72 countries in the world. This allowed ranking countries by the level of their scientific development and grouping them by scientific results and scientific potential. Three groups of countries were identified: catching-up countries by the science development level, potential leaders in science development and leaders by the science development level. Economic security indicators were modeled according to the scientific development level in the groups of countries. The models developed allow forecasting the values of economic security indicators depending on the scientific developments management in the country.
Keywords: Scientific development; scientific development index; modelling; economic security.